Using mixed methods to understand and tackle barriers to accessing health services - Natalia Houghton; Ernesto Bascolo; Andrés Coitiño; Theadora S. Koller; James Fitzgerald (Pan American Health Organization, 2023)
This report describes the experience and lessons learnt from designing and implementing a combined quantitative and qualitative method to assess barriers to accessing health services. This approach was developed to study barriers to access in five dimensions: availability; geographical, financial, and organizational accessibility; acceptability; contact; and effective coverage. The study design was used in six countries in the World Health Organization Region of the Americas. The findings highlight the importance of having a well defined analysis framework and the benefits of adopting a mixed-methods approach. Using existing data and contextualizing findings according to specific population groups and geographical areas were essential for relevance and utilization of the study outcomes. The findings demonstrate the feasibility of using mixed methods to understand the complexity of access problems faced by different subpopulations. By involving decision-makers from the beginning and allowing flexibility for sustained discussions, the analysis and findings had an impact. The engagement of health authorities and key stakeholders facilitated the use of the findings for collaborative identification of policy options to eliminate access barriers. Lessons learnt from the study emphasized the need for active participation of decision-makers, flexibility in the process, and sustained opportunities for discussion to ensure impact. Giving consideration to local priorities and adapting the methods accordingly were important for the relevance and use of the findings. Future efforts could consider incorporating mixed methods into national and local monitoring and evaluation systems.